Kaidah Fiqh: Konsep Murabahah Dalam Perbankan Syariah - Nuranisya, Siti; Januri, Fauzan; Al-Hakim, Sofyan (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
This study discusses murabahah contracts from the perspective of fiqh muamalah rules and their implementation in Islamic banking in Indonesia. Murabahah is a sale and purchase contract with the principle of transparency of the cost price and profit margin that is clearly agreed upon between the seller and the buyer, in accordance with the principles of justice and the prohibition of usury in Islam. This study uses a normative legal method with a literature review to understand the legal basis and requirements of murabahah contracts. The results of the study show that murabahah contracts must meet the validity requirements such as tamyiz, ta'addud at-tarfain, tatabuq al-iradatain, ittihad at-tarfain, wujud al-mal 'inda al-'aqd or al-qudrah 'ala at-taslim, salahiyah al-mal li at-ta'amuli, at-ta'yin au qabiliyyah al-mahal li at-ta'amuli, and must not contain adamu mukhalafah asy-syari'i. However, Islamic banking practices often face obstacles, such as unclear ownership of goods and a lack of transparency regarding profit margins, which reduces customer trust. This study recommends strengthening internal supervision and public education to align murabahah contract practices with the objectives of Sharia. Thus, murabahah can become an effective Islamic financial instrument in supporting the economic growth of the community, especially the MSME sector in Indonesia, in a fair manner and in accordance with Islamic principles.